2004
DOI: 10.1073/pnas.0404679101
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for conservation of architecture and physical properties of Omp85-like proteins throughout evolution

Abstract: Omp85-like proteins represent a family of proteins involved in protein translocation, and they are present in all domains of life, except archaea. In eukaryotes, Omp85-like proteins have been demonstrated to form tetrameric pore-forming complexes that interact directly with their substrate proteins. Studies performed with bacterial Omp85-like proteins have demonstrated pore-forming activity but no evidence of multimerization. In this article, we characterize the Haemophilus influenzae HMW1B protein, an Omp85-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 47 publications
4
70
0
Order By: Relevance
“…For instance, nOmp85 forms complexes with a putative trimeric structure (Fig. 1) similar to that of other known PTBs from proteobacteria (23,38). We have shown that the N-terminal domain is required for the complex formation in vitro (Fig.…”
Section: Relationship Between Prokaryotic and Eukaryotic Members Of Tmentioning
confidence: 87%
“…For instance, nOmp85 forms complexes with a putative trimeric structure (Fig. 1) similar to that of other known PTBs from proteobacteria (23,38). We have shown that the N-terminal domain is required for the complex formation in vitro (Fig.…”
Section: Relationship Between Prokaryotic and Eukaryotic Members Of Tmentioning
confidence: 87%
“…In fact, in both the channel and concerted model the later stages of translocation such as the dissociation of Hbp from BamA are difficult to reconcile with a monomeric BamA. Interestingly, BamA and BamA-like proteins have been shown to oligomerize in vitro (Paschen et al, 2003;Robert et al, 2006;Surana et al, 2004), suggesting the existence of a hydrophobic central cavity as an insertion site for OMPs docked to the Bam complex by SurA. The binding of SurA could then trigger conformational changes of the Bam complex to accommodate an 'expanded', loosely folded bbarrel in that hydrophobic core.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the swelling rate performed with a range of different size sugars gave an estimation of the size of the pore around 2.7 nm. The specific activities are much lower than for OmpF, suggesting that the pores are either of smaller size than the general diffusion porins (which is unlikely based on the estimated pore size) or remain mainly closed (21). The integrity of the periplasmic domain was shown to be essential for secretion, and thus this region is postulated to participate in substrate recognition and/or interaction (20).…”
mentioning
confidence: 99%
“…By using epitope tagging and accessibility to engineered cysteines, St. Geme and co-workers (21) showed that the N terminus is surface-exposed and followed by a large periplasmic domain and then finally by a C-terminal domain consisting of a ␤-barrel with 10 -13 transmembrane ␤ strands. Liposome swelling assays suggested that HMW1B and the C-terminal domain have pore forming activity.…”
mentioning
confidence: 99%